A lanthanum-containing tungsten rod blank and its preparation method and application

By adding cricket oxides to the tungsten alloy and controlling the grain size, the tungsten rod -containing billet is prepared to solve the problem of low tungsten filament -resistant strength and easy deformation, and the tungsten alloy wire with high strength and high -performance is achieved.

CN116275048BActive Publication Date: 2025-01-24CMT RARE METAL ADVANCED MATERIALS (HUNAN) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310285290.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-22
Publication Date
2025-01-24
Estimated Expiration
2043-03-22

AI Technical Summary

Technical Problem

The existing tungsten wire has low room temperature tensile strength and is prone to deformation and compressive defects, which affects its performance.

Method used

Using lanthanum-containing tungsten rod blanks, by adding lanthanum oxide to the tungsten alloy, the mass percentage of lanthanum oxide is controlled between 0.05% and 0.5%, and the average grain size is controlled to be above 5000/mm2.

Benefits of technology

It improves the tensile resistance of tungsten alloy silk, and through the particle reinforcement effect of the element element, it relieves the stress concentration of the crystal world micro -crack, and enhances the overall strength of the tungsten alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004139579540000161
    Figure BDA0004139579540000161
Patent Text Reader

Abstract

The invention discloses a lanthanum-containing tungsten rod blank and a preparation method and application thereof, and relates to the technical field of tungsten products. The lanthanum-containing tungsten rod blank is made of a tungsten alloy; the tungsten alloy includes lanthanum oxide; the mass percentage of lanthanum oxide in the tungsten alloy is 0.05% to 0.5%; the average grain size of the lanthanum-containing tungsten rod blank is 5000 grains / mm 2 The tungsten alloy of the present invention is prepared by adding lanthanum to tungsten. Lanthanum is used as a strengthening element. On the one hand, lanthanum is distributed on the grain boundary of the matrix, which effectively prevents the growth of grains; thereby achieving the control of the average grain size of the lanthanum-containing tungsten rod blank, so that the final tungsten alloy wire has high strength; on the other hand, lanthanum element particles are distributed in the matrix on the grain boundary in a spherical shape, which effectively alleviates the stress concentration of microcracks at the grain boundary of the tungsten alloy, plays a role in particle strengthening, and improves the strength of the tungsten alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of tungsten products, and in particular is a lanthanum-containing tungsten rod blank and a preparation method and application thereof. Background Art

[0002] Pure tungsten has the characteristics of low-temperature brittleness and poor grain structure uniformity, which leads to insufficient strength of tungsten materials. Especially when tungsten materials are prepared into filaments or blade shapes, they have defects such as insufficient strength, easy deformation and low pressure resistance.

[0003] In the related art, tungsten wire is generally prepared by the following method:

[0004] The tungsten rod blank is processed into a tungsten rod with a diameter of about 3mm by rotary forging; and then further processed into tungsten wires of various thicknesses by die drawing. That is, the performance of the tungsten rod blank will have a great influence on the performance of the tungsten wire; and the room temperature tensile strength of the tungsten wire in the related art is 3000MPa~4000MPa, that is, the tungsten wire prepared from the tungsten rod blank in the related art has a low strength.

[0005] Therefore, the present invention provides a lanthanum-containing tungsten rod blank to solve the problems raised in the above background technology. Summary of the invention

[0006] The object of the present invention is to provide a lanthanum-containing tungsten rod blank to solve at least one aspect of the problems and defects raised in the above background technology.

[0007] The present invention also provides a method for preparing the lanthanum-containing tungsten rod blank.

[0008] The present invention also provides application of the lanthanum-containing tungsten rod blank.

[0009] Specifically, the first aspect of the present invention provides a lanthanum-containing tungsten rod blank, wherein the lanthanum-containing tungsten rod blank is made of tungsten alloy;

[0010] The tungsten alloy includes lanthanum oxide;

[0011] The mass percentage of lanthanum oxide in the tungsten alloy is 0.05% to 0.5%;

[0012] The average grain size of the lanthanum-containing tungsten rod blank is 5000 / mm 2 above.

[0013] According to one of the technical solutions of the lanthanum-containing tungsten rod blank of the present invention, at least the following beneficial effects are achieved:

[0014] The tungsten alloy of the present invention is prepared by adding lanthanum to tungsten. Lanthanum is used as a strengthening element. On the one hand, lanthanum is distributed on the grain boundary of the matrix, which effectively prevents the growth of grains; thereby, the average grain size of the lanthanum-containing tungsten rod blank is controlled, so that the strength of the finally prepared tungsten alloy wire is high; on the other hand, lanthanum element particles are distributed on the grain boundary in the matrix in a spherical shape, which effectively alleviates the stress concentration of microcracks at the grain boundary of the tungsten alloy, plays a role in particle strengthening, and improves the strength of the tungsten alloy.

[0015] According to some embodiments of the present invention, the mass percentage of lanthanum oxide in the tungsten alloy is 0.06% to 0.5%.

[0016] According to some embodiments of the present invention, the mass percentage of lanthanum oxide in the tungsten alloy is 0.1% to 0.5%.

[0017] According to some embodiments of the present invention, the mass percentage of lanthanum oxide in the tungsten alloy is 0.12% to 0.5%.

[0018] According to some embodiments of the present invention, the mass percentage of lanthanum oxide in the tungsten alloy is 0.15% to 0.5%.

[0019] According to some embodiments of the present invention, the mass percentage of lanthanum oxide in the tungsten alloy is 0.18% to 0.5%.

[0020] According to some embodiments of the present invention, the mass percentage of lanthanum oxide in the tungsten alloy is 0.2% to 0.5%.

[0021] According to some embodiments of the present invention, the mass percentage of lanthanum oxide in the tungsten alloy is 0.25% to 0.5%.

[0022] According to some embodiments of the present invention, the mass percentage of lanthanum oxide in the tungsten alloy is 0.25% to 0.45%.

[0023] According to some embodiments of the present invention, the mass percentage of lanthanum oxide in the tungsten alloy is 0.25% to 0.4%.

[0024] According to some embodiments of the present invention, the mass percentage of lanthanum oxide in the tungsten alloy is 0.25% to 0.35%.

[0025] According to some embodiments of the present invention, the mass percentage of lanthanum oxide in the tungsten alloy is 0.25% to 0.3%.

[0026] According to some embodiments of the present invention, the mass percentage of lanthanum oxide in the tungsten alloy is 0.26% to 0.3%.

[0027] According to some embodiments of the present invention, the mass percentage of lanthanum oxide in the tungsten alloy is 0.28% to 0.3%.

[0028] The present invention can improve the performance of the lanthanum-containing tungsten rod blank by increasing the lanthanum oxide content. However, when the mass content of lanthanum oxide is greater than 0.5%, the difficulty of subsequent processing will be greatly increased.

[0029] According to some embodiments of the present invention, the lanthanum oxide is lanthanum trioxide (La2O3).

[0030] According to some embodiments of the present invention, the particle size of the lanthanum oxide is below 1.0 μm.

[0031] The particle size of lanthanum oxide is less than 1.0 μm through microscopic analysis. The particle size of lanthanum oxide is small and evenly dispersed at the grain boundary and in the grain of tungsten crystal. It is not easy to break prematurely to form a crack source during subsequent processing, and it is beneficial to coordinate the deformation of tungsten crystal grains.

[0032] According to some embodiments of the present invention, the average particle size of the lanthanum oxide is 0.3 μm to 1.0 μm.

[0033] According to some embodiments of the present invention, the average particle size of the lanthanum oxide is 0.5 μm to 1.0 μm.

[0034] According to some embodiments of the present invention, the tungsten alloy further includes at least one of rhenium oxide and cerium oxide.

[0035] According to some embodiments of the present invention, the mass fraction of the rhenium oxide is 0.15% to 0.2%.

[0036] According to some embodiments of the present invention, the mass fraction of the cerium oxide is 0.05% to 0.1%.

[0037] According to some embodiments of the present invention, the rhenium oxide is Re2O3.

[0038] According to some embodiments of the present invention, the cerium oxide is CeO2.

[0039] According to some embodiments of the present invention, the density of the lanthanum-containing tungsten rod blank is 18.6 g / cm 3 above.

[0040] According to some embodiments of the present invention, the density of the lanthanum-containing tungsten rod blank is 18.65 g / cm 3 above.

[0041] According to some embodiments of the present invention, the density of the lanthanum-containing tungsten rod blank is 18.7 g / cm 3 above.

[0042] According to some embodiments of the present invention, the density of the lanthanum-containing tungsten rod blank is 18.75 g / cm 3 above.

[0043] According to some embodiments of the present invention, the density of the lanthanum-containing tungsten rod blank is 18.7 g / cm 3 ~18.85g / cm 3 .

[0044] The density of lanthanum-containing tungsten rod blanks in related technologies is generally 17.2g / cm 3 ~17.6g / cm 3 , there are many pores and continuous pore defects in the structure, which are easy to form crack sources during the processing; and there are often abnormally grown tungsten grains in the structure, and the grains are unevenly deformed in the subsequent deep processing process, forming crack sources; wire breakage is easy to occur during the drawing process, resulting in a low actual yield. The present invention controls the density of the lanthanum-containing tungsten rod blank to make the tungsten grain structure uniform and free of abnormally grown grains, further improving the actual yield.

[0045] According to some embodiments of the present invention, the average grain size of the lanthanum-containing tungsten rod blank is 6000 grains / mm 2 above.

[0046] According to some embodiments of the present invention, the average grain size of the lanthanum-containing tungsten rod blank is 7000 grains / mm 2 above.

[0047] According to some embodiments of the present invention, the average grain size of the lanthanum-containing tungsten rod blank is 8000 grains / mm 2 above.

[0048] According to some embodiments of the present invention, the average grain size of the lanthanum-containing tungsten rod blank is 9000 grains / mm 2 above.

[0049] According to some embodiments of the present invention, the average grain size of the lanthanum-containing tungsten rod blank is 10,000 grains / mm 2 above.

[0050] According to some embodiments of the present invention, the average grain size of the lanthanum-containing tungsten rod blank is 6000 grains / mm 2 ~15000pcs / mm 2 .

[0051] According to some embodiments of the present invention, the average grain size of the lanthanum-containing tungsten rod blank is 6000 grains / mm 2 ~9000pcs / mm 2 .

[0052] In unit volume, the grain boundary area of ​​fine-grained metals is large, and deformation or cracks will encounter more grain boundary obstacles when moving in the metal.

[0053] The second aspect of the present invention provides a method for preparing the above-mentioned lanthanum-containing tungsten rod blank, comprising the following steps:

[0054] S1, mixing the first tungsten powder and the lanthanum-containing solution and performing ultrasonic-assisted drying to obtain a pretreated tungsten powder;

[0055] S2, reducing the pretreated tungsten powder to obtain alloy powder;

[0056] S3, mixing the alloy powder and the second tungsten powder, cold isostatic pressing and sintering;

[0057] The sintering temperature is 2400°C to 2600°C.

[0058] According to one technical solution of the preparation method technical solution of the present invention, at least the following beneficial effects are achieved:

[0059] The preparation method of the present invention comprises the following steps: mixing a lanthanum-containing solution and a first tungsten powder and then drying the mixture with the assistance of ultrasound. During the drying process, lanthanum compound grains in the lanthanum-containing solution will precipitate; under the action of ultrasound, the energy of the ultrasound acts on the grains, thereby breaking the grains, thereby increasing the number of nuclei and fully refining the grains of the lanthanum compound; at the same time, under the action of ultrasound, the agglomerated tungsten powder can also be effectively broken, so that the tungsten particles can be refined.

[0060] The tungsten alloy powder obtained by reduction in step S2 of the present invention has a small particle size, a high proportion of fine end particle size in the particle size distribution, and a high sintering activity, and is easy to increase the degree of accumulation and growth of lanthanum oxide particles in the subsequent sintering process.

[0061] The present invention prepares the final required alloy powder by solid-solid mixing the alloy powder prepared by reduction with the second tungsten powder of suitable particle size. The alloy powder after solid-solid mixing has a narrow particle size distribution range and a small average particle size, which is conducive to the subsequent sintering of a lanthanum-containing tungsten rod blank with high density, uniform structure and small lanthanum oxide particle size.

[0062] The present invention also controls the diffusion rate of atoms by controlling the sintering temperature, thereby further controlling the crystal phase structure, thereby further improving the strength of the tungsten alloy wire finally obtained.

[0063] According to some embodiments of the invention, the lanthanum-containing solution comprises a lanthanum nitrate solution.

[0064] According to some embodiments of the present invention, the molar concentration of the lanthanum nitrate solution is 0.5 mol / L to 0.6 mol / L.

[0065] According to some embodiments of the present invention, the lanthanum-containing solution further comprises at least one of a cerium nitrate solution and a rhenium nitrate solution.

[0066] According to some embodiments of the present invention, the molar concentration of the cerium nitrate solution is 0.5 mol / L to 0.6 mol / L.

[0067] According to some embodiments of the present invention, the molar concentration of the rhenium nitrate solution is 0.5 mol / L to 0.6 mol / L.

[0068] According to some embodiments of the present invention, the power of the ultrasound is 200W to 300W.

[0069] According to some embodiments of the present invention, the drying temperature is below 110°C.

[0070] According to some embodiments of the present invention, the drying temperature is 100°C to 110°C.

[0071] According to some embodiments of the present invention, the drying time is 6 hours to 8 hours.

[0072] According to some embodiments of the present invention, the reduction temperature is 700°C to 800°C.

[0073] According to some embodiments of the present invention, the reduction time is 5 h to 7 h.

[0074] According to some embodiments of the present invention, the reducing atmosphere is hydrogen.

[0075] According to some embodiments of the present invention, the average particle size of the alloy powder is 1.5 μm to 2.0 μm.

[0076] According to some embodiments of the present invention, the average particle size of the alloy powder is 1.7 μm to 2.0 μm.

[0077] According to some embodiments of the present invention, the particle size of lanthanum oxide in the alloy powder is below 0.3 μm.

[0078] According to some embodiments of the present invention, in step S3, the alloy powder and the second tungsten powder are mixed to obtain a mixed alloy powder.

[0079] According to some embodiments of the present invention, the average particle size of the second tungsten powder is 1.0 μm to 2.5 μm.

[0080] According to some embodiments of the present invention, the average particle size of the mixed alloy powder is 1.0 μm to 2.5 μm.

[0081] According to some embodiments of the present invention, D90 of the mixed alloy powder is below 15 μm.

[0082] According to some embodiments of the present invention, the diameter distance of the mixed alloy powder is less than 1.8.

[0083] According to some embodiments of the present invention, the mixing time in step S3 is 5 h to 10 h.

[0084] According to some embodiments of the present invention, the mixing speed in step S3 is 20 r / min to 30 r / min.

[0085] According to some embodiments of the present invention, the mixing speed in step S3 is 25 r / min.

[0086] According to some embodiments of the present invention, the cold isostatic pressing obtains a green compact.

[0087] According to some embodiments of the present invention, the cold isostatic pressing pressure is 150 MPa to 200 MPa.

[0088] According to some embodiments of the present invention, the unit weight of the green compact is 2.0 kg to 4.0 kg.

[0089] According to some embodiments of the present invention, the sintering atmosphere is a protective atmosphere.

[0090] According to some embodiments of the present invention, the protective atmosphere is hydrogen.

[0091] According to some embodiments of the present invention, the temperature is increased before sintering.

[0092] According to some embodiments of the present invention, the temperature raising procedure is as follows:

[0093] The first stage of heating: from 20℃~30℃ to 1000℃~1100℃, the heating time is 8h~12h;

[0094] The first stage of heat preservation: keep warm at 1000℃~1100℃ for 0.5h~1.5h;

[0095] The second stage of heating: from 1000℃~1100℃ to 1800℃~2000℃, the heating time is 6h~8h;

[0096] The second stage of heat preservation: keep warm at 1800℃~2000℃ for 1.5h~2.5h;

[0097] The third stage of heating: from 1800℃~2000℃ to 2400℃~2600℃, the heating time is 2h~3h.

[0098] According to some embodiments of the present invention, the sintering time is 10 h to 12 h.

[0099] The third aspect of the present invention provides the use of the above-mentioned lanthanum-containing tungsten rod blank in the preparation of tungsten wire.

[0100] According to some embodiments of the present invention, the wire diameter of the tungsten wire is less than 20 μm.

[0101] According to some embodiments of the present invention, the tensile strength of the tungsten wire is above 5800 MPa.

[0102] According to some embodiments of the present invention, the tensile strength of the tungsten wire is above 6000 MPa.

[0103] According to some embodiments of the present invention, the tensile strength of the tungsten wire is above 6200 MPa.

[0104] According to some embodiments of the present invention, the tensile strength of the tungsten wire is above 6400 MPa.

[0105] According to some embodiments of the present invention, the tensile strength of the tungsten wire is above 6500 MPa.

[0106] According to some embodiments of the present invention, the tensile strength of the tungsten wire is 5800 MPa to 7000 MPa.

[0107] According to some embodiments of the present invention, the lanthanum-containing tungsten rod blank is used in the field of preparing cutting wires. DETAILED DESCRIPTION

[0108] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0109] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0110] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0111] Example 1

[0112] This embodiment is a lanthanum-containing tungsten rod blank, which is composed of the following components by mass fraction:

[0113] La2O3 0.35% and W 99.65%.

[0114] The density of the lanthanum-containing tungsten rod blank is 18.82 g / cm 3 ;

[0115] The average grain size of the lanthanum-containing tungsten rod blank is 7200 grains / mm 2 ;

[0116] The average particle size of La2O3 in the lanthanum-containing tungsten rod blank is 0.5 μm;

[0117] The lanthanum-containing tungsten rod blank has a uniform structure;

[0118] The diameter of the lanthanum-containing tungsten rod blank is 18.5 mm.

[0119] The preparation method of the lanthanum-containing tungsten rod blank in this embodiment consists of the following steps:

[0120] S1. Doping:

[0121] Lanthanum nitrate solution (molar concentration of 0.5 mol / L) and blue tungsten powder (particle size of 2 μm to 20 μm) are mixed, and after sufficient mixing (mixing time of 0.5 h), the blue tungsten doping solution is ultrasonically dried (drying temperature of 110° C., drying time of 7 h, ultrasonic power of 200 W) to obtain a doping material;

[0122] S2. Restore:

[0123] The doped material prepared in S1 was reduced (reduction temperature was 700°C, reduction time was 6 hours, and reduction atmosphere was hydrogen) into alloy powder (average particle size was 1.8 μm);

[0124] S3, solid-solid doping:

[0125] The alloy powder prepared by S2 and pure tungsten powder (average particle size of 2.3 μm) were placed in a powder batcher for mixing (mixing time of 6 h, speed of 25 r / min) to obtain mixed alloy powder (average particle size of 2.1 μm, D90 of 13 μm, and diameter distance of 1.8);

[0126] S4. Suppression:

[0127] The mixed alloy powder obtained in step S3 is cold isostatically pressed into a rod-shaped compact (with a diameter of 22 mm and a unit weight of 2.5 kg);

[0128] The pressure of cold isostatic pressing in this step is 200MPa;

[0129] S5. Sintering:

[0130] The rod-shaped compact prepared by S4 was heated and sintered (the atmosphere was hydrogen, the sintering temperature was 2500°C, and the sintering time was 11 hours) to obtain a lanthanum-containing tungsten rod blank;

[0131] The heating procedure in this step is as follows:

[0132] The first stage of heating: from 20℃ to 1000℃, the heating time is 8h;

[0133] The first stage of heat preservation: keep warm at 1000℃ for 1h;

[0134] The second stage of heating: from 1000℃ to 1800℃, the heating time is 6h;

[0135] The second stage of heat preservation: keep warm at 1800℃ for 2h;

[0136] The third stage of heating: from 1800℃ to 2500℃, the heating time is 2h.

[0137] Example 2

[0138] This embodiment is a tungsten rod blank containing lanthanum. This embodiment is a tungsten rod blank containing lanthanum. The tungsten rod blank containing lanthanum is composed of the following components by mass fraction:

[0139] La2O3 0.4% and W 99.6%.

[0140] The density of the lanthanum-containing tungsten rod blank is 18.77 g / cm 3 ;

[0141] The average grain size of the lanthanum-containing tungsten rod blank is 6800 grains / mm 2 ;

[0142] The average particle size of La2O3 in the lanthanum-containing tungsten rod blank is 0.45 μm;

[0143] The lanthanum-containing tungsten rod blank has a uniform structure;

[0144] The diameter of the lanthanum-containing tungsten rod blank is 18.5 mm.

[0145] The method for preparing the lanthanum-containing tungsten rod blank in this embodiment is different from that in Embodiment 1 in that the amount of lanthanum nitrate solution used is adjusted according to the doping amount.

[0146] Example 3

[0147] This embodiment is a lanthanum-containing tungsten rod blank, which is composed of the following components by mass fraction:

[0148] La2O3 0.5% and W 99.5%.

[0149] The density of the lanthanum-containing tungsten rod blank is 18.71 g / cm 3 ;

[0150] The average grain size of the lanthanum-containing tungsten rod blank is 6500 / mm 2 ;

[0151] The average particle size of La2O3 in the lanthanum-containing tungsten rod blank is 0.4 μm;

[0152] The lanthanum-containing tungsten rod blank has a uniform structure;

[0153] The diameter of the lanthanum-containing tungsten rod blank is 18.5 mm.

[0154] The method for preparing the lanthanum-containing tungsten rod blank in this embodiment is different from that in Embodiment 1 in that the amount of lanthanum nitrate solution used is adjusted according to the doping amount.

[0155] Example 4

[0156] This embodiment is a lanthanum-containing tungsten rod blank, which is composed of the following components by mass fraction:

[0157] Re2O3 0.15%, La2O3 0.2% and W 99.65%.

[0158] The density of the lanthanum-containing tungsten rod blank is 18.75 g / cm 3 ;

[0159] The average grain size of the lanthanum-containing tungsten rod blank is 7400 grains / mm 2 ;

[0160] The average particle size of La2O3 in the lanthanum-containing tungsten rod blank is 0.32 μm;

[0161] The lanthanum-containing tungsten rod blank has a uniform structure;

[0162] The diameter of the lanthanum-containing tungsten rod blank is 18.5 mm.

[0163] The preparation method of the lanthanum-containing tungsten rod blank in this embodiment is different from that in Embodiment 1 in that the lanthanum nitrate solution is replaced by a mixed solution of lanthanum nitrate and rhenium nitrate (the molar concentration of lanthanum ions is 0.5 mol / L, the molar concentration of rhenium ions is 0.5 mol / L, and the dosage is adjusted according to the doping amount).

[0164] Example 5

[0165] This embodiment is a lanthanum-containing tungsten rod blank, which is composed of the following components by mass fraction:

[0166] CeO2 0.1%, Re2O3 0.2%, La2O3 0.05% and W 99.65%.

[0167] The density of the lanthanum-containing tungsten rod blank is 18.79 g / cm 3 ;

[0168] The average grain size of the lanthanum-containing tungsten rod blank is 8200;

[0169] The average particle size of La2O3 in the lanthanum-containing tungsten rod blank is 0.3 μm;

[0170] The lanthanum-containing tungsten rod blank has a uniform structure;

[0171] The diameter of the lanthanum-containing tungsten rod blank is 18.5 mm.

[0172] The preparation method of the lanthanum-containing tungsten rod blank in this embodiment is different from that in Embodiment 1 in that the lanthanum nitrate solution is replaced by a mixed solution of lanthanum nitrate, cerium nitrate and rhenium nitrate (the molar concentration of lanthanum ions is 0.5 mol / L, the molar concentration of rhenium ions is 0.5 mol / L, and the molar concentration of cerium ions is 0.5 mol / L, and the dosage is adjusted according to the doping amount).

[0173] Comparative Example 1

[0174] This comparative example is a lanthanum-containing tungsten rod blank, which is composed of the following components by mass fraction:

[0175] La2O3 0.03% and W 99.97%.

[0176] The density of the lanthanum-containing tungsten rod blank is 18.43 g / cm 3 ;

[0177] The average grain size of the lanthanum-containing tungsten rod blank is 4100 grains / mm 2 ;

[0178] The average particle size of La2O3 in the lanthanum-containing tungsten rod blank is 1.2 μm;

[0179] The microstructure uniformity of the lanthanum-containing tungsten rod blank is poor;

[0180] The diameter of the lanthanum-containing tungsten rod blank is 18.5 mm.

[0181] The preparation method of the lanthanum-containing tungsten rod blank in this comparative example is different from that in Example 1 in that the amount of lanthanum nitrate solution used is adjusted according to the doping amount.

[0182] Comparative Example 2

[0183] This comparative example is a lanthanum-containing tungsten rod blank, which is composed of the following components by mass fraction:

[0184] La2O3 0.6% and W 99.4%.

[0185] The density of the lanthanum-containing tungsten rod blank is 18.47 g / cm 3 ;

[0186] The average grain size of the lanthanum-containing tungsten rod blank is 4600;

[0187] The average particle size of La2O3 in the lanthanum-containing tungsten rod blank is 1.5 μm;

[0188] The microstructure uniformity of the lanthanum-containing tungsten rod blank is poor;

[0189] The diameter of the lanthanum-containing tungsten rod blank is 18.5 mm.

[0190] The preparation method of the lanthanum-containing tungsten rod blank in this comparative example is different from that in Example 1 in that the amount of lanthanum nitrate solution used is adjusted according to the doping amount.

[0191] Comparative Example 3

[0192] This comparative example is a lanthanum-containing tungsten rod blank, which is composed of the following components by mass fraction:

[0193] La2O3 0.35% and W 99.65%.

[0194] The density of the lanthanum-containing tungsten rod blank is 18.38 g / cm 3 ;

[0195] The average grain size of the lanthanum-containing tungsten rod blank is 3500 / mm 2 ;

[0196] The particle size of La2O3 in the lanthanum-containing tungsten rod blank is 2.1 μm;

[0197] The lanthanum-containing tungsten rod blank has a uniform structure;

[0198] The diameter of the lanthanum-containing tungsten rod blank is 18.5 mm.

[0199] The preparation method of the lanthanum-containing tungsten rod blank in this comparative example consists of the following steps:

[0200] S1. Doping:

[0201] Lanthanum nitrate solution (molar concentration of 0.5 mol / L) and blue tungsten powder (particle size of 2 μm to 20 μm) are mixed, and after sufficient mixing (mixing time of 0.5 h), the blue tungsten doping solution is ultrasonically dried (drying temperature of 110° C., drying time of 7 h, ultrasonic power of 200 W) to obtain a doping material;

[0202] S2. Restore:

[0203] The doped material prepared in S1 was reduced (reduction temperature was 700°C, reduction time was 6 hours, and reduction atmosphere was hydrogen) into alloy powder (average particle size was 1.8 μm);

[0204] S3, solid-solid doping:

[0205] The alloy powder prepared by S2 and pure tungsten powder (average particle size of 2.3 μm) were placed in a powder batcher for mixing (mixing time of 6 h, speed of 25 r / min) to obtain mixed alloy powder (average particle size of 2.1 μm, D90 of 13 μm, and diameter distance of 1.8);

[0206] S4. Suppression:

[0207] The mixed alloy powder obtained in step S3 is cold isostatically pressed into a rod-shaped compact (with a diameter of 22 mm and a unit weight of 2.5 kg);

[0208] The pressure of cold isostatic pressing in this step is 200MPa;

[0209] S5. Sintering:

[0210] The rod-shaped compact prepared by S4 was heated and sintered (the atmosphere was hydrogen, the sintering temperature was 2500°C, and the sintering time was 11 hours) to obtain a lanthanum-containing tungsten rod blank;

[0211] The heating procedure in this step is as follows:

[0212] The temperature was raised from 20°C to 2500°C, and the heating time was 12h.

[0213] Comparative Example 4

[0214] This comparative example is a lanthanum-containing tungsten rod blank, which is composed of the following components by mass fraction:

[0215] La2O3 0.35% and W 99.65%.

[0216] The density of the lanthanum-containing tungsten rod blank is 18.78 g / cm 3 ;

[0217] The average grain size of the lanthanum-containing tungsten rod blank is 4800 grains / mm 2 ;

[0218] The average particle size of La2O3 in the lanthanum-containing tungsten rod blank is 0.6 μm;

[0219] The lanthanum-containing tungsten rod blank has a uniform structure;

[0220] The diameter of the lanthanum-containing tungsten rod blank is 18.5 mm.

[0221] The preparation method of the lanthanum-containing tungsten rod blank in this comparative example consists of the following steps:

[0222] S1. Doping:

[0223] Lanthanum nitrate solution (molar concentration of 0.5 mol / L) and blue tungsten powder (particle size of 2 μm to 20 μm) are mixed, and after sufficient mixing (mixing time of 0.5 h), the blue tungsten doping solution is ultrasonically dried (drying temperature of 110° C., drying time of 7 h, ultrasonic power of 200 W) to obtain a doping material;

[0224] S2. Restore:

[0225] The doped material prepared in S1 was reduced (reduction temperature was 700°C, reduction time was 6 hours, and reduction atmosphere was hydrogen) into alloy powder (average particle size was 1.8 μm);

[0226] S3, solid-solid doping:

[0227] The alloy powder prepared by S2 and pure tungsten powder (average particle size of 2.3 μm) were placed in a powder batcher for mixing (mixing time of 6 h, speed of 25 r / min) to obtain mixed alloy powder (average particle size of 2.1 μm, D90 of 13 μm, and diameter distance of 1.8);

[0228] S4. Suppression:

[0229] The mixed alloy powder obtained in step S3 is cold isostatically pressed into a rod-shaped compact (with a diameter of 22 mm and a unit weight of 2.5 kg);

[0230] The pressure of cold isostatic pressing in this step is 200MPa;

[0231] S5. Sintering:

[0232] The rod-shaped compact prepared by S4 was heated and sintered (the atmosphere was hydrogen, the sintering temperature was 2300°C, and the sintering time was 11 hours) to obtain a lanthanum-containing tungsten rod blank;

[0233] The heating procedure in this step is as follows:

[0234] The first stage of heating: from 20℃ to 1000℃, the heating time is 8h;

[0235] The first stage of heat preservation: keep warm at 1000℃ for 1h;

[0236] The second stage of heating: from 1000℃ to 1800℃, the heating time is 6h;

[0237] The second stage of heat preservation: keep warm at 1800℃ for 2h;

[0238] The third stage of heating: from 1800°C to 2300°C, the heating time is 1h.

[0239] A series of tests were performed on the lanthanum-containing tungsten rod blanks of Examples 1 to 5 and Comparative Examples 1 to 4: density measurement was performed to obtain the density of the sintered lanthanum-containing tungsten rod blanks; grain size detection was performed to obtain the average grain size; and tungsten wire (wire diameter of 20 μm) was obtained by drawing the lanthanum-containing tungsten rod blanks to test the tensile strength of the tungsten wire; the experimental results are shown in Table 1.

[0240] Table 1 Density, grain size and corresponding tensile strength of tungsten wires obtained from examples 1 to 5 and comparative examples 1 to 4

[0241]

[0242] In summary, the tungsten alloy of the present invention is prepared by adding lanthanum to tungsten. Lanthanum is used as a strengthening element. On the one hand, lanthanum is distributed on the grain boundaries of the matrix, effectively preventing the growth of grains; thereby achieving the control of the average grain size of the lanthanum-containing tungsten rod blank, so that the final tungsten alloy wire has high strength; on the other hand, lanthanum element particles are distributed in the matrix on the grain boundaries in a spherical shape, effectively alleviating the stress concentration of microcracks at the grain boundaries of the tungsten alloy, and playing a role in particle strengthening, thereby improving the strength of the tungsten alloy.

[0243] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A tungsten rod blank containing lanthanum, characterized in that: The lanthanum-containing tungsten rod blank is made of tungsten alloy; The tungsten alloy includes lanthanum oxide; The mass percentage of lanthanum oxide in the tungsten alloy is 0.05% to 0.5%; The average grain size of the lanthanum-containing tungsten rod blank is 5000 / mm 2 above; The method for preparing the lanthanum-containing tungsten rod blank comprises the following steps: S1, mixing the first tungsten powder and the lanthanum-containing solution and performing ultrasonic-assisted drying to obtain a pretreated tungsten powder; S2, reducing the pretreated tungsten powder to obtain alloy powder; S3, mixing the alloy powder and the second tungsten powder, cold isostatic pressing and sintering; The sintering temperature is 2400°C to 2600°C; The heating procedure before sintering is as follows: The first stage of heating: from 20℃~30℃ to 1000℃~1100℃, the heating time is 8h~12h; The first stage of heat preservation: keep warm at 1000℃~1100℃ for 0.5h~1.5h; The second stage of heating: from 1000℃~1100℃ to 1800℃~2000℃, the heating time is 6h~8h; The second stage of heat preservation: keep warm at 1800℃~2000℃ for 1.5h~2.5h; The third stage of heating: from 1800℃~2000℃ to 2400℃~2600℃, the heating time is 2h~3h; The first tungsten powder is blue tungsten powder; The second tungsten powder is pure tungsten powder.

2. The lanthanum-containing tungsten rod blank according to claim 1, characterized in that: The average particle size of the lanthanum oxide is less than 1.0 μm.

3. The lanthanum-containing tungsten rod blank according to claim 1, characterized in that: The tungsten alloy also includes at least one of rhenium oxide and cerium oxide.

4. The lanthanum-containing tungsten rod blank according to claim 1, characterized in that: The density of the lanthanum-containing tungsten rod blank is 18.6 g / cm 3 above.

5. The lanthanum-containing tungsten rod blank according to claim 1, characterized in that: The power of the ultrasound is 200W~300W.

6. The lanthanum-containing tungsten rod blank according to claim 1, characterized in that: The cold isostatic pressing pressure is 150 MPa to 200 MPa.

7. The lanthanum-containing tungsten rod blank according to claim 1, characterized in that: The average particle size of the alloy powder is 1.5 μm to 2.0 μm.

8. The lanthanum-containing tungsten rod blank according to claim 1, characterized in that: The average particle size of the second tungsten powder is 1.0 μm to 2.5 μm.

9. Use of the lanthanum-containing tungsten rod blank according to any one of claims 1 to 8 in the preparation of tungsten wire.

Citation Information

Patent Citations

  • Method for preparing rare-earth oxide dispersion strengthened fine-grained tungsten material

    CN105518169A